SURVEI KEPUASAN MAHASISWA DALAM LAYANAN AKADEMIK DAN NON AKADEMIK FAKULTAS USHULUDDIN ADAB DAN DAKWAH - aulia, Siti Aulia Nabila; Sulvinajayanti; Fitrana, Andi Dian; Umairah, Jiehan Putri (Journal of Media and Communication Studies, 2025)
Siti Aulia Nabila. A. Student Satisfaction Survey in Academic and Non-Academic Services of the Faculty of Ushuluddin Adab and Da'wah (supervised by Mrs. Sulvinajayanti and Mrs. Andi Dian Fitriana) Students are an important part of a university and are also the main focus of the teaching and service process at the university. The success of students in achieving their academic goals reflects the success of the university in providing quality education and supporting services. This thesis discusses "a survey of student satisfaction in academic and non-academic services of the Faculty of Ushuluddin Adab and Da'wah". This study aims to determine the level of student satisfaction in academic and non-academic services of the Faculty of Ushuluddin Adab and Da'wah, and to determine what factors influence student satisfaction in academic and non-academic services of the Faculty of Ushuluddin Adab and Da'wah. This study uses a quantitative approach whose data are numbers processed using descriptive analysis and using the 10% slovin formula with a sample of 306 students as representatives of the population.